2006
DOI: 10.4321/s0213-61632006000400004
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric treatments for children and adolescents preferred by spanish psychiatrists

Abstract: To study the prescription criteria of Spanish psychiatrists treating children and adolescents. Methods: a survey was designed to record their first choice and complementary preferences for pharmacological, psychotherapeutic and psychoeducational interventions in five disorders: autism, depression, separation anxiety, obsessive compulsive and attentiondeficit/hyperactivity disorders. Results: One hundred and nine psychiatrists responded. No distinction was made between children and adolescents. Around 90% recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Psychotropic drug utilisation appears to be greatest in the USA, but evidence from prescription data suggests that the UK saw a particularly large increase (68%) in the number of psychotropic prescriptions for young people under 18 years of age between 2000 and 2002 (Wong et al, 2004). In some studies, antidepressants have been found to be the most commonly prescribed class of psychotropic medication (Dean, McDermot, & Marshall, 2006; Toro, Mur, & Cantó, 2006; Aras, Tas, & Unlu, 2006). Although most attention has focused on the increasing use of antipsychotics and drugs for ADHD, there is also evidence of an increase in antidepressant usage in the years leading up to 2003 (Zito et al, 2002; Najjar et al, 2004; Katz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychotropic drug utilisation appears to be greatest in the USA, but evidence from prescription data suggests that the UK saw a particularly large increase (68%) in the number of psychotropic prescriptions for young people under 18 years of age between 2000 and 2002 (Wong et al, 2004). In some studies, antidepressants have been found to be the most commonly prescribed class of psychotropic medication (Dean, McDermot, & Marshall, 2006; Toro, Mur, & Cantó, 2006; Aras, Tas, & Unlu, 2006). Although most attention has focused on the increasing use of antipsychotics and drugs for ADHD, there is also evidence of an increase in antidepressant usage in the years leading up to 2003 (Zito et al, 2002; Najjar et al, 2004; Katz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Of the 48 respondents, all prescribed some psychotropic medication but there was wide variation in the volume of prescriptions, although 88% were prescribing antidepressants at that time. In a national Spanish survey of child and adolescent psychiatrists conducted in 2002 (response rate 11.4%), 84% of respondents reported their treatment of choice for depression was a combination of psychotropics (almost always antidepressants) and psychotherapy (Toro et al, 2006). Only 0.9% believed that psychotherapy alone should be used.…”
Section: Introductionmentioning
confidence: 99%